Metode akuisisi dalam pengembangan bahan pustaka di Perpustakaan Al-Ghazali Universitas Nahdlatul Ulama Al-Ghazali Cilacap - Pingki Rofiyanti Setianingsih; Labibah Labibah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study discusses the method of acquiring library materials at the Al-Ghazali Library, Nahdlatul Ulama Imam Al-Ghazali University Cilacap, the aim is to see the process of acquiring the library materials. This research method uses qualitative methods, with a case study at the Al-Ghazali Unugha Cilacap library. Data collection techniques through interviews and literature study. The conclusion that can be drawn is that the Al-Ghazali Unugha Cilacap library carries out the process of developing a collection of library materials through three stages, starting with the purchasing process, in this process the purchase is not determined by the time, unless the librarian makes an Annual Work Plan and Budget (RAT) first. The second stage is receiving grants or gifts from other institutions, this stage the Unugha library receives grants from the Asia Foundation, and the third is the exchange of resources, this stage the Unugha library collaborates with several surrounding universities such as UIN Saizu Purwokerto, Cilacap State Polytechnic and Cilacap Regional Library. The obstacles experienced by the Al-Ghazali Unugha Cilacap library, such as the uncertainty of purchasing books in large quantities or in large quantities due to limited budget funds